Tathbīq At-Ṭarīqah At-Tawāṣuliyyah Li Tarqiyah Mahārah Al-Kalām Ladā Ṭhullāb Ash-Ṣaff Ats-Tsāmin Bi Al-Madrasah Ats-Tsānawiyyah Al-Ahliyyah Al-Jam‘Iyyah Al-Waṣliyyah Tembung - Beby Khairani; Zulheddi Zulheddi (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2025)
This research is motivated by the problem of low students' maharah kalam ability, therefore the purpose of this study aims to determine the application of communicative methods in improving the maharah kalam ability of grade 8 students of Mts Al-Jam'iyatul Al-Wasliyah Tembung which includes how to apply it and the results of the application of the learning method. The research method used in this study is descriptive qualitative with a case study approach. Data collection techniques in this study are interviews, observation and documentation. Data analysis techniques used in this study include data reduction, data presentation and drawing conclusions. The results of this study indicate that there is an update in the study, namely there is an explanation that has not been in previous studies, such as inhibiting and supporting factors for the application of communicative methods. The application of communicative methods can improve the maharah kalam of grade 8 students of Mts Al-Jam'iyatul Al-Wasliyah Tembung, this is evidenced by supporting aspects such as fluency in speaking, pronunciation, sentence structure, appropriateness, vocabulary mastery, self-confidence and questions and answers. The implementation of the communicative method experiences difficulties felt by Arabic language teachers, namely low basic Arabic language skills of students, low interest and motivation to learn, difficulty in achieving curriculum targets and different student abilities. However, these various difficulties can be resolved through supporting factors in the implementation of the communicative method, namely complete facilities, several students who have high interest and motivation to learn, and subject matter that is relevant to everyday life.